Factores clínicos laboratoriales y sobrevida en pacientes hospitalizados con diabetes mellitus tipo 2 infectados por SARS - CoV2 en Iquitos 2020 - Parimango Alvarez, Marcos Hugo (2023)
Type 2 Diabetes Mellitus (T2DM) and SARS-COV2 infection are associated with increased severity and mortality in hospitalized patients. Therefore, the objective of our study was to determine the clinical, laboratory and survival factors in hospitalized patients with type 2 diabetes mellitus infected by SARS-COV2 in Iquitos. A quantitative, cross-sectional study was carried out that evaluated a retrospective cohort of hospital medical records during the year 2020 and involved records of 150 patients with DM2 and SARS-COV2. The Kaplan Meier test and Cox regression with the SPSS 25 tool were used. The results show that the survival time of 50% of the patients was 12 days and a mortality of 35%. Survival time was associated with age over 65 years and presence of cough P <0.05. It was concluded that survival time was related to age and presence of cough.